A view on the pre-service didactic formation of the foreign language teacher - Camacho Delgado, Alfredo A.; Mora Lorenzo, Consuelo; Pérez Companioni, Milena (Varela Journal, 2012)
This article deals with the undergraduate education of teachers of foreign languages in Cuba in terms of didactic competence, basing on a developmental theory of teaching and l earning rooted in Vigotskian ideas and a communicative theory of language. On these bases the authors characterize the process of teacher education of the foreign language teachers-to-be.